THE SOCIOLINGUISTIC ANALYSIS OF CODE-MIXING TYPES IN LIVY RENATA AND NIRINA ZUBIR’S UTTERANCES IN “TS MEDIA” PODCAST - Juni Arta Sagala; Agustina Sihombing; Gaguk Rudianto (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2022)
This research examined the code-mixing found on YouTube. Because many people nowadays use YouTube to express their creativity, this article used YouTube. The aims of this research were to determine the types of code-mixing and the code-mixing factors that influence children in south Jakarta to mix their language. The researchers choose the data source from TS Media’s YouTube, Livy Renata's utterance in the video was used the most. This research was revealed by the researchers using Muysken’s theory. The qualitative descriptive method was used in the research to analyze the different types of code-mixing and the dominant category used by Livy's utterance. Data were gathered through observation. The data was derived from a video that was uploaded to TS Media's YouTube channel. There are (8) insertions, (4) alternation, and (3) congruent lexicalization as a consequence of this research. They all use varying amounts of code-mixing in their speakers' and listeners' utterances. In this video, there are so many mixes in language and the researchers finding revealed that insertion was the most common type of code-mixing used by speakers and hearers in the video TS media's YouTube. It was followed by the second type, alternation, and the last type, congruent lexicalization.